2020
DOI: 10.1007/s10815-020-01710-z
|View full text |Cite
|
Sign up to set email alerts
|

The use of autologous platelet-rich plasma (PRP) versus no intervention in women with low ovarian reserve undergoing fertility treatment: a non-randomized interventional study

Abstract: Purpose To investigate the impact of a 3-month course of intracortical injections of autologous platelet-rich plasma (PRP) upon ovarian reserve markers versus no intervention in women with low ovarian reserve prior to undergoing assisted reproductive technology (ART). Methods Prospective controlled, non-randomized comparative study conducted in a private fertility clinic, in Venezuela. Women with abnormal ovarian reserve markers (FSH, AMH and AFC) who declined oocyte donation were allocated to one of the follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
77
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 48 publications
4
77
2
1
Order By: Relevance
“…Interestingly, recent data demonstrated that PRP intraovarian infusion may improve ovarian reserve in POR patients of advanced age [60]. Melo and colleagues showed a significant improvement in AMH levels and AFC during the first three months of the follow-up period, while participants presented with a higher clinical pregnancy rate compared to the control group [60]. In our study, we report an overall clinical pregnancy rate of 46.6% following PRP treatment.…”
Section: Discussionsupporting
confidence: 49%
See 4 more Smart Citations
“…Interestingly, recent data demonstrated that PRP intraovarian infusion may improve ovarian reserve in POR patients of advanced age [60]. Melo and colleagues showed a significant improvement in AMH levels and AFC during the first three months of the follow-up period, while participants presented with a higher clinical pregnancy rate compared to the control group [60]. In our study, we report an overall clinical pregnancy rate of 46.6% following PRP treatment.…”
Section: Discussionsupporting
confidence: 49%
“…In our study, we report an overall clinical pregnancy rate of 46.6% following PRP treatment. Our participants were on average three years younger, and subjected to ICSI treatment on the third month following a single PRP treatment in contrast to the study of Melo et al, 2020 in which patients were subjected to ART treatment within a 12-month time-frame [60]. Considering results presented in the study of Melo et al, 2020 as well as in ours, it seems that PRP treatment may be effective in POR patients of both young and advanced age.…”
Section: Discussioncontrasting
confidence: 48%
See 3 more Smart Citations